2014
DOI: 10.3109/13697137.2014.966949
|View full text |Cite
|
Sign up to set email alerts
|

The estrogen receptor as a mediator of the pathological actions of cholesterol in breast cancer

Abstract: Despite increased survivorship among patients, breast cancer remains the most common cancer among women, and is the second leading cause of cancer death in women. The magnitude of this problem provides a strong impetus for new chemopreventative strategies and/or lifestyle changes that reduce cancer incidence. It is of significance, therefore, that several studies positively correlate obesity to the development of breast cancer. Importantly, obesity is also highly associated with elevated cholesterol, and chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 51 publications
0
27
0
2
Order By: Relevance
“…More than half of elderly persons have elevated levels of blood cholesterol and triglyceride, which was not a serious problem for cancer in the past. But recently, several studies showed that cholesterol itself is a risk factor for cancer [16], and patients taking statins were found having a lower breast cancer incidence and decreased recurrence [17]. Moreover, cholesterol can activate substrate-stimulated ABCG2 ATPase activity and direct vesicular substrate transport [13].…”
Section: Discussionmentioning
confidence: 99%
“…More than half of elderly persons have elevated levels of blood cholesterol and triglyceride, which was not a serious problem for cancer in the past. But recently, several studies showed that cholesterol itself is a risk factor for cancer [16], and patients taking statins were found having a lower breast cancer incidence and decreased recurrence [17]. Moreover, cholesterol can activate substrate-stimulated ABCG2 ATPase activity and direct vesicular substrate transport [13].…”
Section: Discussionmentioning
confidence: 99%
“…Hypercholesterolemia is an established clinical side effect of aromatase inhibitor (AI) therapy. Given the revelations about the estrogenic cholesterol metabolite 27HC, this phenomenon may counteract the intended effects of AIs . Breast cancer patients experiencing hypercholesterolemia during AI treatment may thus benefit from concomitant cholesterol‐lowering treatment to reduce the probability of 27HC‐driven ER actions.…”
Section: Statins and Response To Endocrine Therapy In Breast Cancermentioning
confidence: 99%
“…oestradiol), it is likely to play a crucial role in hormone (oestrogen)‐dependent breast cancer. Importantly, 27HC, the oxysterol produced from cholesterol, is involved in the regulation of intracellular cholesterol homeostasis , but also acts as an endogenous selective oestrogen receptor modulator capable of increasing the growth and metastasis of tumours . Valuable clinical insight into the impact of statin treatment on 27HC in breast cancer patients was gained through collaboration with the McDonnell Lab at Duke University , where biological samples from our “window‐of‐opportunity” statin trial were analysed.…”
Section: Statins and Response To Endocrine Therapy In Breast Cancermentioning
confidence: 99%
“…It is important to keep in mind that the approximate IC 50 of 27HC for the ERs is 1μM [6]. 27HC is synthesized from cholesterol by CYP27A1, a mitochondrial P450 enzyme, which is primarily expressed in liver and cells of the myeloid immune lineage such as macrophages [40]. 27HC is metabolized by CYP7B1, another P450 enzyme that is expressed primarily in the brain, liver and other peripheral organs [41].…”
Section: 27-hydroxycholesterol An Endogenous Sermmentioning
confidence: 99%